Current and historical concentrations of poly and perfluorinated compounds in sediments of the northern Great Lakes – Superior, Huron, and Michigan. (May 2018) - Codling, Garry; Hosseini, Soheil; Corcoran, Margaret B.; Bonina, Solidea; Lin, Tian; Li, An; Sturchio, Neil C.; Rockne, Karl J.; Ji, Kyunghee; Peng, Hui; Giesy, John P.
Abstract: Current and historical concentrations of 22 poly- and perfluorinated compounds (PFASs) in sediment collected from Lake Superior and northern Lake Michigan in 2011 and Lake Huron in 2012 are reported. The sampling was performed in two ways, Ponar grabs of surface sediments for current spatial distribution across the lake and dated cores for multi-decadal temporal trends. Mean concentrations of the sum of PFASs (∑PFASs) were 1.5, 4.6 and 3.1 ng g −1 dry mas (dm) in surface sediments for Lakes Superior, Michigan and Huron, respectively. Of the five Laurentian Lakes, the watersheds of Superior and Huron are the less densely populated by humans, and concentrations observed were typically less and from more diffuse sources, due to lesser urbanization and industrialization. However, some regions of greater concentrations were observed and might indicate more local, point sources. In core samples concentrations ranged from <LOQ to 46.6 ng g −1 dm among the three lakes with concentrations typically increasing with time. Distributions of PFASs within dated cores largely corresponded with increase in use of PFASs, but with physiochemical characteristics also affecting distribution. Perfluoroalkyl sulfonates (PFSAs) with chain lengths >7 that include perfluoro-n-octane sulfonate (PFOS) bind more strongly to sediment, which resulted in more accurate analyses of temporal trends. Shorter-chain PFASs, such as perfluoro-n-butanoic acid which is the primary replacement for C8 PFASs that have been phased out, are more soluble and were identified in some core layers at depths corresponding to pre-production periods. Thus, analyses of temporal trends of these more soluble compounds in cores of sediments were less accurate. Total elemental fluorine (TF) and extractable organic fluorine (EOF) indicated that identified PFASs were not a significant fraction of fluorine containing compounds in sediment (<0.01% in EOF). Graphical abstract: Image 1 Highlights: The 2 least populated Great Lakes have long-term PFC exposure. Local sources in some sites may be key to concentrations. Short-chain PFCs may not be measured reliably in sediment cores. An increase in PFCs fits well with historical use. Trends in use are less well characterized in sediment from deeper waters. Abstract : This Publication looks at the temporal and spatial trends of PFASs in the Northern Great Lakes. It incorporates additional work of total and extractable fluorine to identify the total fluorinated material that is unknown and the physical characteristics that may explain some of the observed trends.